EVALUACIÓN DE RIESGOS Y SU INCIDENCIA EN EL DESEMPEÑO LABORAL DE LOS OPERADORES EN LA EMPRESA MAINDUSTRIAS S.A. DEL CANTÓN QUEVEDO - Navarro Chávez, Darwin Alberto (2023)
This study focuses on risk assessment and its impact on the work performance of operators in the company Maindustrias S.A. in the canton of Quevedo. Field research was carried out to gather information on the company's safety processes and practices. A questionnaire was also applied to the workers to obtain their opinion about the perception of risks in their work and their work performance.